2016
DOI: 10.3109/17483107.2015.1129455
|View full text |Cite
|
Sign up to set email alerts
|

Gait training of subacute stroke patients using a hybrid assistive limb: a pilot study

Abstract: Purpose To determine whether gait training with a hybrid assistive limb (HAL) as an exoskeleton robotic device was safe and could increase functional mobility and gait ability in subacute stroke patients. Methods The participants were eight patients with post-stroke hemiparesis whose walking impairment and gait recovery curves had plateaued. The intervention program was gait training using HAL and a walker for 20 min daily 5 days a week for 5 weeks. The 10-m maximum walking speed (MWS), self-selected walking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 64%
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 64%
“…In an exploratory study, Yoshikawa et al (2016) suggested that HAL treatment in cases of sub-acute stroke may enhance the walking speed by changing the walking pattern and asymmetry ratio in the late recovery stage. Mizukami et al (2017) also argued that, if gait treatment with HAL can be started early, walking with an appropriate pattern can be improved and patients can avoid acquiring an incorrect or compensatory walking pattern. Early intensive HAL treatment may contribute not only to improved independent walking but also to improved walking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effects of locomotion training using HAL ® for stroke patients (Kawamoto et al, 2013;Nilsson, Vreede, Häglund, Kawamoto, Sankai, & Borg, 2014;Watanabe, Tanaka, Inuta, Saitou, & Yanagi, 2014;Mizukami et al, 2016). Kawamoto et al (2013) reported that the dependent ambulatory levels (FAC 2-3 with chronic stroke) showed significant differences in comfortable walking speed between before and after a total of 16 HAL ® training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…During locomotor training, the patients walked on a floor and were harnessed in a mobile suspension system. Mizukami et al (2016) discussed that the harness walker system enabled patients to walk continuously without risk of falling. Therefore, the use of mobile suspension system played an important role in enhancing the HAL ® training effect.…”
Section: Discussionmentioning
confidence: 99%